Tiktok Marketing Strategy To Increase Brand Awareness Of Products At PT. Ayo Menebar Kebaikan - Galang Duta Amalsyah; Anas Hidayat (Cita konsultindo, 2024)
This research was carried out to understand whether there is effectiveness of TikTok in building brand awareness. This research is based on the TikTok phenomenon which has become the most popular social media platform, especially among the millennial generation. Thus, examining how TikTok marketing features can build consumer brand awareness can provide valuable insight into their impact on consumer behavior. This research can provide insight into how companies can build brand awareness which can then increase product sales. This research applies descriptive qualitative research with interview methodology and direct observation carried out through an internship process. The conclusion of this research is that the company implemented a strategy through social media Tiktok by showing that this strategy had a positive impact on consumer interest during the internship period.